Efektifitas Arang Batok Kelapa dalam Menurunkan Kadar Nikel, E Coli, dan Kekeruhan pada Air Sumur Gali - Idayani Sangadjisowohy; Sumiati Tomia; Jasman Jasman; Risman S. Duka (Jurnal Sehat Mandiri, 2025)
Water is essential for human life, as it plays a crucial role in various biological processes within the body, with water constituting 50-70% of total body weight. This study aimed to assess the effectiveness of coconut shell charcoal in reducing levels of nickel, E. coli, and turbidity in dug well water. An experimental research design with a "Pre-Post Test Design" was employed. The study was conducted in Lelilef Village, Central Halmahera Regency, using 70 dug wells as samples. Ten liters of water from each well were filtered using coconut shell charcoal, which was locally sourced from the village. Purposive sampling was applied in selecting the wells for filtration. The results indicated that coconut shell charcoal filtration significantly reduced nickel levels by 98.6%, decreased E. coli levels in 64.3% of the samples, and successfully met water turbidity standards. Conclusion : The use of coconut shell charcoal is effective in reducing nickel, E. coli, and turbidity in contaminated well water.